The Role of Bronchoscopy in Hemoptysis - Sakina Sakina; Irmi Syafa'ah (Faculty of Medicine Universitas Airlangga, 2020)
Massive hemoptysis is a medical emergency that requires intensive treatment with appropriate therapy. The underlying causes of hemoptysis are airway disease, parenchymal disease, and vascular disease. An appropriate diagnostic modality is needed in handling hemoptysis, one of which is by bronchoscopy. Bronchoscopy can identify whether bleeding is still active and see the condition of the patient’s respiratory tract. Apart from being a diagnostic tool, bronchoscopy is also used as one of the therapeutic methods to stop bleeding. Initial bronchoscopy should be performed on massive hemoptysis after the patient is stable and the other side of the lung that is not the source of bleeding has been protected. After the source of bleeding is seen, several therapies can be done.